YENİ BİR DAMAR OLUŞUMU ŞEKLİNDE GELİŞMİŞ ARTERİO-VENÖZ FİSTÜL - İRİZ, Erkan and KALAYCIOĞLU, Sedat and SİNCİ, Volkan (Cerrahpaşa Medical Journal, 2014)
Background and Design.- The pseudotract of traumatic A-V fistulas is a fibrotic formation externally. Inside the tract there is a neointima layer formed by increasing flow and pressure. In our case the tract was including the three layers of an artery. We decided to report this case because it is interesting and value to discuss. A 59 year old man who carried out CABP operation applied to our outpatient clinic because of pain and distends of his right arm since the operation. We examined the patient and decided surgical treatment for the diagnosis of traumatic A-V fistula. Surgery performed with local anesthesia. We saw a connection between brachial artery and basilic vein, with about 1 cm in length. This formation was resected by ligation of two sides. The hystopathological research of that segment reported as the structure included three layers of normal vessel. Acquired traumatic A-V fistulas are mostly grown up with an anastomosis line without neovascularization. In this case the A-V fistula formed by approximately 1 cm. vascular connection between artery and vein. We didn’t see any case in literature. Meanwhile, the A-V fistulas were reviewed.